Therapeutic potential of promiscuous targets in Mycobacterium tuberculosis. (October 2018) - Lee, Bei Shi; Pethe, Kevin
Graphical abstract: Schematic diagram of the Mycobacterium tuberculosis cell wall. Promiscuous targets QcrB, MmpL3, and DprE1 are membrane-associated proteins. Their localisation may be a contributing factor to the high hit rates in screening assays. Their 'promiscuity' reflect the essentiality of the cell wall biosynthesis as well as the oxidative phosphorylation pathways in mycobacterial growth and survival. Highlights: Target promiscuity is merely a reflection of bias in screening assays. Promiscuous targets represent pathogen's vulnerabilities both in vitro and in vivo. Their inhibitors have therapeutic potential for inclusion in rational drug combinations. Abstract : In the field of tuberculosis drug development, the term 'promiscuous' was coined to collectively describe targets that repeatedly show up in whole-cell screenings. With the current climate leaning towards the exclusion of these targets in future drug screens, this review discusses and clarifies misconceptions surrounding this classification, the prospects of developing compounds targeting promiscuous targets, and their potential impact on tuberculosis drug development. The dominance of these targets in cell-based screens reflect not only bias introduced by experimental setup, but also some of the pathogen's greatest vulnerabilities. Coupled with favourable predictions of their in vivo efficacies and synergism with other TB drugs, these targets open opportunities to be explored for the development of rational drug combination for tuberculosis.